Formation of Phosphate Crystals from Cow Urine Using Aeration System Batch Reactor - Fadilah, Reza; Hanifah, Windia; Cendekia, Devy; Ramandani, Adityas Agung (CHEMICA: Jurnal Teknik Kimia, 2023)
The waste generated from the livestock sector is cow urine containing nitrogen, sulfur, phosphate, ammonium, sodium, manganese, iron, silica, chlorine, magnesium and calcium. The aim of this research is to reduce phosphate levels which will have an impact on the environment caused by cow urine which contains phosphate and ammonium and forms phosphate crystals using a batch reactor with an aeration system. The results of wastewater treatment using a batch reactor produce precipitate in the form of phosphate crystals which can be used as fertilizer for plants. This study used a completely randomized design (CRD) with two repetitions, namely with a comparison of the rate of aeration (air flow) 1 Lpm, 1.5 Lpm and 2 Lpm with the time used, namely 0 minutes, 60 minutes, 120 minutes, 180 minutes and 240 minute. Based on research that has been done, the highest aeration rate (air flow) in phosphate removal in cow urine waste is at 1 Lpm air flow with a time of 240 minutes and a phosphate removal efficiency of 84.8822%. Meanwhile, at an air flow of 1.5 Lpm with a time of 60 minutes and a phosphate removal efficiency of 95.4315%. At an air flow of 2 Lpm with a time of 240 minutes, the removal efficiency can only be 34.3421%. The content of phosphate crystals obtained from the XRF results was obtained at 3.173%. At an air flow of 2 Lpm with a time of 240 minutes, the removal efficiency can only be 34.3421%. The content of phosphate crystals obtained from the XRF results was obtained at 3.173%. At an air flow of 2 Lpm with a time of 240 minutes, the removal efficiency can only be 34.3421%. The content of phosphate crystals obtained from the XRF results was obtained at 3.173%.